Comparison of the volatiles composition between healthy and buprestid infected Juglans regia (Juglandaceae). (2020)
Meliboeus ohbayashii primoriensis (Coleoptera: Buprestidae) is an important pest of the walnut tree Juglans regia (Juglandaceae), but the volatiles mediating this plant–herbivore interaction are unknown. In this study, volatiles emitted by healthy J. regia and by plants infested with M. ohbayashii primoriensis (Coleoptera: Buprestidae) were obtained by a dynamic headspace method and analyzed by gas chromatography-mass spectrometry (Shanxi, China). We identified 26 major compounds and compared the volatile composition of healthy and buprestid-infected J. regia. Green leaf volatiles were detected in all damaged plants, including the monoterpenoids β-phellandrene and (E)-β-ocimene, the sesquiterpenoids (-)-β-bourbonene, β-ylangene, and (E,E)-α-farnesene, the alcohols linalool, myrtenol, and (E)-(-)-pinocarveol, the ketones (E)-pinocamphone and (Z)-pinocamphone, and the ester methyl salicylate. The major volatiles detected in healthy plants were β-pinene (36.26 %), α-pinene (23.81 %), D-limonene (12.03 %), sabinene (8.63 %), and β-myrcene (4.35 %). The main volatiles from M. ohbayashii primoriensis larva-infested plants were β-pinene (37.82 %), α-pinene (20.36 %), D-limonene (14.71 %), germacrene D (5.24 %), sabinene (4.52 %), and β-phellandrene (3.80 %). These results enrich our understanding of volatiles of healthy plants and plants infested with M. ohbayashii primoriensis. Furthermore, they provide a theoretical basis and scientific foundation for integrated pest management and for effective ecologically sustainable pest control strategies